Estudio comparativo de las herramientas de metodologías ágiles para el aplicar buenas prácticas de desarrollo en la calidad de software. - Yánez Triana, Cinthia Karina (2022)
Nowadays, companies have the need to automate their processes, which choose to implement information systems in their departments, in order to be able to process efficiently and in optimal time. Poor quality software always poses risks. The causes that affect the quality of software are the result of bad practices in development. Despite the advantages offered by software development under an agile approach, there are aspects related to quality assurance that still need to be addressed. This document has been developed using a bibliographical research approach, in which the consultation in indexed internet databases, different tools of agile methodologies for development, is evidenced. In the modern software industry, delivering high quality software is the main goal for software developers. This case study provides a comparison between the most popular agile methodologies, Scrum, Extreme Programming and Kanban. There is a significant need for developers to know more about the quality of the software produced. Companies must consider that the main problem during the software development process is the change in functional specifications, followed by very optimistic planning and that the use of agile methodologies will allow them to have greater flexibility in the changes required.